Response of Breonadia salicina in the Sabie River to an extreme flood: implications for demographic modelling, monitoring and adaptive river management in the Kruger National Park - Dowson, Lisa (My University, 2009)
The Sabie River is a heterogeneous river system and sedimentation has been identified as a threat which may reduce bedrock influence and heterogeneity in this river. This motivated the development of a monitoring programme utilising the demographic profiles of Breonadia salicina (B. salicina) as an indicator of sediment change along the Sabie River. The negative-J demographic profile of B. salicina in the pool-rapid channel type was considered the most sensitive to sedimentation. As part of this monitoring programme, a rule based model was developed as a predictive tool to be used by managers. The Breonadia Model was designed to model changes in the demographic profile in response to changes in sedimentation. In February 2000, an extreme flood occurred in the Sabie River and markedly altered the biophysical template and influenced the structure of the B. salicina population. The Breonadia model was developed prior to the 2000 flood and there were no empirical data on vegetation response to a flood of this magnitude. Hence, the model may not fully represent the process of vegetation response and recovery as it occurs on the post flood biophysical template. The 2000 flood in the Sabie River provided an opportunity for examining the response of B. salicina to a Large Infrequent flood and for directly testing how well the Breonadia Model predicts these responses. The B. salicina population was always considered to follow a flowering response, producing seeds in order to recover from disturbance. This characteristic was incorporated in the Breonadia Model, with the model subsequently being used to predict the likely timeframe of recovery to a Large Infrequent flood disturbance. This study aimed to improve understanding of B. salicina population dynamics subsequent to large infrequent floods by examining the different response strategies of the B. salicina population after the 2000 large infrequent flood event. This study also reevaluated the application of the negative-J demographic profile-focused Breonadia Model. Assessments were made of the applicability of the Breonadia Model and monitoring in the pool-rapid channel type within the context of the SAM framework utilised in the KNP. The examination of response mechanisms revealed that sprouting is an important mechanism in B. salicina that enabled the population to recover from damage caused by the flood. A canonical correspondence analysis showed that sprouting accounted for 56% of the overall variation in recovery response five years after the flood. Flowering accounted for the other 44%. The likelihood of sprouting was higher in more severe damage categories and smaller size-class categories. These response mechanisms were unrelated to the underlying iii geomorphology at the channel type scale. Thus, while recruitment has been shown to occur in relation to the underlying physical template, the mode of response is related to individual size-class and damage severity. The complex interplay of biotic responses and the multiscaled physical template suggests that the longer term recovery of the B. salicina population in the Sabie River will not be spatially uniform. The Breonadia Model did not withstand direct testing and predicted an overly optimistic level of recruitment following a catastrophic flood event. The data suggest that sprouting continues to limit flowering in adult plants five years after the 2000 flood, therefore limiting recruitment of new individuals. Thus the Breonadia Model was updated to take the influence of sprouting on fecundity into account. A penalty to fecundity was determined from field data and extrapolated to include the 10 years after any catastrophic flood. This study has revealed the importance of disturbance events in influencing response mechanisms, which has an effect the demography of a riparian species. The physical template of the Sabie River forms a complex and patchy template on which riparian vegetation processes occur. However, factors unrelated to the physical template also play a role in influencing riparian vegetation processes. Management of the Sabie River needs to take these complex relationships into account in the context of the variable hydrological regime in order to update and apply valid management strategies to the system.